'Factors associated with high and low levels of school exclusions: comparing the English and wider UK experience'. Issue 4 (2nd October 2019) - Cole, Ted; McCluskey, Gillean; Daniels, Harry; Thompson, Ian; Tawell, Alice
ABSTRACT: This article draws on findings from the first cross-national study of school exclusions in the four jurisdictions of the UK. It sketches factors associated with the past research with reductions in exclusions. It then reports interview data gathered in England in 2018 from five specialist officers working in two Local Authorities and a senior officer working for a national voluntary organisation. The officers describe good practice but also national, local and school level developments contributing to a deteriorating situation. These developments include unhelpful government guidance and regulations; school accountability frameworks affecting curriculum and leading to the neglect of Special Educational Needs; loss of Local Authority powers and funding resulting in reductions in support services. Data gathered for this study in other UK jurisdictions suggests that in Scotland and Northern Ireland, and to a lesser extent in Wales, a practice that avoids school exclusions has persisted more than in England.